Pengaruh Komunikasi, Kesehatan Mental dan Disiplin Kerja Terhadap Kinerja Karyawan Administrasi PT Astra Isuzu Lampung dalam Perspektif Bisnis Islam: Studi pada Karyawan Administrasi PT Astra Isuzu Lampung - Delsy Oktavia; Evi Ekawati; Agus Kurniawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of communication, mental health, and work discipline on the performance of administrative employees at PT Astra Isuzu Lampung from the perspective of Islamic business. This research is motivated by the importance of qualified human resources in improving company productivity through effective communication, good mental health, and strong work discipline in accordance with Islamic values such as honesty, responsibility, and trustworthiness. The study employed a quantitative method with descriptive and verificative approaches, involving all administrative employees of PT Astra Isuzu Lampung as the research population using saturated sampling techniques. Data were collected through questionnaires, observations, and documentation, and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The results show that communication, mental health, and work discipline each have a positive and significant effect on employee performance, and simultaneously these variables significantly influence the performance of administrative employees at PT Astra Isuzu Lampung. From the perspective of Islamic business, effective communication, maintaining mental health, and implementing work discipline reflect Islamic work ethics that contribute to improving work quality and creating a harmonious and productive work environment